THE EFFECT OF SERVICE QUALITY AND HOSPITAL FACILITIES ON HOSPITAL IMAGE MEDIATED BY INPATIENT SATISFACTION AT S HOSPITAL BOGOR - Margaretha Cecilia; Wani Devita Gunardi; Eka Desy Purnama (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
In the competitive hospital industry environment, patient satisfaction serves as an important benchmark for the quality of services and facilities provided by hospitals. Patient satisfaction becomes a key determinant of a hospital's image in the eyes of the public. The purpose of this study is to analyze the influence of the quality of services and hospital facilities on the hospital's image, with patient satisfaction acting as a mediating variable. The research design is cross-sectional, employing a quantitative research method. The population in this study includes the inpatients at Hospital S in Bogor. The sampling method used probability sampling with a simple random sampling technique. Data collection was conducted using a questionnaire. Data analysis was performed using SEM-PLS. The results of the study indicate that the quality of service, hospital facilities, and patient satisfaction have a positive and significant impact on the hospital's image. The study also shows patient satisfaction mediates the relationship between the quality of service and hospital facilities and the hospital's image. This means that good quality service and hospital facilities will enhance patient satisfaction, which also indirectly improves the hospital's positive image in the eyes of the public.